13. Malnutrition status and related factors in gastric cancer patients undergoing chemotherapy treatment at Ho Chi Minh City oncology hospital - Bich, Nguyen Ngoc; Dao, Pham Hoang; Trinh, Le Thi Diem; Quang, Pham Duy (Tạp chí Nghiên cứu Y học, 2023)
Chemotherapy is one type of systemic treatment for cancer that causes side effects on eating and energy supply, leading to weight loss and malnutrition. Detecting malnutrition early in gastric cancer patients plays a critical role in implementing an effective nutritional regimen that can improve their nutritional status, prevent weight loss, and enhance their ability to withstand and respond to chemotherapy. The cross-sectional study was performed on 95 patients in Ho Chi Minh City Oncology Hospital from October 2021 to June 2022. According to the PG-SGA, MUAC, and BMI, the percentage of malnutrition are 69.5%, 33.7%, and 31.6%, respectively. There is a statistically significant connection between malnutrition rate by PG-SGA with age categories, cancer treatment methods, side effects of chemotherapy, and anemia.